1987
DOI: 10.1152/jappl.1987.63.2.576
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of aged men to head-up tilt during heat exposure

Abstract: The effects of age on cardiovascular and thermoregulatory responses to passive tilting were investigated using six old (61-73 yr) and 10 young (21-39 yr) unacclimatized men. Experiments were carried out at 26 degrees C and after exposure to 40 degrees C and 40% relative humidity for 105 min. Continuous measurements of esophageal (Tes) and mean skin (Tsk) temperatures and heart rate (HR) were recorded. Other variables studied included blood pressure (BP), forearm blood flow (FBF), and cardiac output (CO), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…A blunted HR response and a smaller increase in peripheral resistance are well documented in the elderly (29)(30)(31)33). In the present study, the magnitude of tachycardia during head-up tilt in elderly subjects was attenuated compared with young subjects.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A blunted HR response and a smaller increase in peripheral resistance are well documented in the elderly (29)(30)(31)33). In the present study, the magnitude of tachycardia during head-up tilt in elderly subjects was attenuated compared with young subjects.…”
Section: Discussionsupporting
confidence: 55%
“…Numerous studies have compared cardiovascular responses to orthostatic stress in elderly and young subjects (28)(29)(30)(31)(32)(33). A blunted HR response and a smaller increase in peripheral resistance are well documented in the elderly (29)(30)(31)33).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that sustaining an equivalent esophageal temperature and mean T sk between younger and older participants is inherently difficult. For example, a previous study (Shiraki et al 1987) found maintaining mean T sk between older and younger males resulted in older participants having a significant higher esophageal temperature. Thus, whilst acknowledging the possibility that small differences in T sk may influence MAP (Wilson et al 2002), we preferentially maintained esophageal temperature above mean skin temperature.…”
Section: Limitationsmentioning
confidence: 94%
“…Numerous studies have compared cardiovascular responses to orthostatic stress (hypovolemic stress, i.e., lower body negative pressure: LBNP) in older and young subjects [3,[6][7][8][9]. A blunted heart rate (HR) response and a smaller increase in peripheral resistance are well documented [3,6,9] in the old.…”
Section: Introductionmentioning
confidence: 99%